PENGARUH BRAND PERCEPTION DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN CAFE D'ORANGE - Ardiansyah Ardiansyah; Jusuf Kuleh; Asnawati Asnawati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study to determine the effect of variables between Brand Perception and Â quality service to Customer Loyalty of Â D'Orange cafe The theoretical basis used by management marketing analysis tools Multiple Regression Liner with 60 samples.The conclusion of this study:The function of multiple linear regression calculation result is Y = 0.062 + 0.444 X1 + 0.535 X2. Brand regression coefficient pereptioan (X1) and quality of service (X2) is positive, meaning that if there is an increase of variable quality Brand perception (X1) and quality of service (X2) will lead to an increase in loyalty to the D 'Orange Cafe.Brand perception positive and significant effect on loyalty to the D 'Orange Cafe, so the hypothesis is acceptedService quality and significant positive effect on customer loyalty at D 'Orange Cafe, so the hypothesis is acceptedKeywords: Brand Perception, Quality of Service, - Consumer Loyalty